2016
DOI: 10.4997/jrcpe.2016.404
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Epidural Blood Patches for Spontaneous Low-Pressure Headaches: A Case Series

Abstract: Patients with a spontaneous cerebrospinal fluid leak, normally at a spinal level, typically present with low-pressure headache. In refractory cases, an epidural blood patch may be attempted. We aimed to assess the efficacy of lumbar epidural blood patching in spontaneous, low-pressure headaches. Methods We retrospectively analysed notes of patients who had an epidural blood patch performed for spontaneous low-pressure headaches in a single centre. Information regarding demographics, radiology and clinic follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The proportion of female individuals was 63% (95% CI, 60%-66%; I 2 = 52.4). Connective tissue disorders, spinal pathologies (ie, osteophytes, disc prolapse, and discogenic micro spurs) and bariatric surgery were identified as risk factors for SIH and reported by several authors …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The proportion of female individuals was 63% (95% CI, 60%-66%; I 2 = 52.4). Connective tissue disorders, spinal pathologies (ie, osteophytes, disc prolapse, and discogenic micro spurs) and bariatric surgery were identified as risk factors for SIH and reported by several authors …”
Section: Resultsmentioning
confidence: 97%
“…Connective tissue disorders, spinal pathologies (ie, osteophytes, disc prolapse, and discogenic micro spurs) and bariatric surgery were identified as risk factors for SIH and reported by several authors. [13][14][15][16][17][18][19][20][21][22][23] Table 1…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of the eight questionnaire respondents experienced less pain, and the mean headache severity dropped from 9/10 to 3/10. Five of the eight patients who returned follow-up questionnaires reported that their headache symptoms had improved over time [17] .…”
Section: Discussionmentioning
confidence: 98%
“…Localization of the site is most important not only for surgical planning but also useful to target the EBP which in turn leads to better outcomes. 4 Traditional avenues of leak site localization have been generally limited to CT and MR myelography and in some centers, radionuclide myelography. Conventional CT and MR myelography result in static images that are adequately diagnostic in only 45-54% of cases.…”
Section: Discussionmentioning
confidence: 99%